LECTURES’ PERCEPTION TOWARD THE NEED OF ENGLISH IN MANAGEMENT ECONOMICS DEPARTMENT OF PEKALONGAN UNIVERSITY - Panuntun, Ida Ayu; Hayati, Rizka (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
This study aimed to describe the English needs of the Economics Management Study Program of Pekalongan University based on the perception of the English lecturers. The research design of this research was descriptive qualitative. The total sample used was 2 English lecturers in the Economics Management study program. The research instrument used was a questionnaire with a measurement scale in the form of numbers. The research data was described through needs, real conditions in the classroom, and the desire of the lecturer. The real conditions of learning in the classroom become a basic guideline for achieving the learning objectives in the target needs. These results were also adjusted to the wishes (Wants). Thus, it could be seen that according to the lecturers 'perception, English was an ability that had to be mastered in order to fulfill the students' self-need to understand the economic context in using English. Moreover, understanding and mastering the material supported students to compete in the world of work. From the lecturers’ perspective, it was known that speaking ability was the most important ability to be owned by students, and the difficulties most often faced by students according to the lecturer was in listening skill.